FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SITINJO KABUPATEN DAIRI TAHUN 2020 - Heriaty Berutu (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Exclusive breastfeeding is an action or activity that babies give breastfeed without additional liquid such as formula milk, oranges, honey, mineral water and without additional food such as banana, papaya, milk, biscuit, and porridge, except vitamin, mineral and medication.Exclusive breastfeeding is good for babies brain growth, most nutrition sources, relieve digestive, immune boosting infant, reduce the risk of obesity and nourish baby's lungs as well. On the other hand, Exclusive breastfeeding also benefits for mothers by economically profitable, durable, confidence to lactating, practical, convenient, delaying pregnancy, relieve overweight, diminution uterus, diminution of breast cancer, uterine cancer, reduce stress and reduce the risk osteoporosis. The factors which related to exclusive breastfeeding has not figured out. The research is descriptive analytical by cross sectional study approach. It analyzes the breastfeeding in region of Public Health Centre Sitinjo of Dairi.The population of research is 118 mothers who have babies 0-6 months in region of Public Health Centre Sitinjoof Dairi. The analysis data is univariate analysis, bivariate analysis Chi-square, and multivariate analysis logistic regression.The results showed age (p = 0,896), level of education (p = 0.582), work (p = 0,545), and income (p = 0,224) are not relevance with exclusive breastfeeding. Knowledge (p = 0.002; Or = 0,285), attitude (p = 0.001; Or = 0,211), place of birth (p = 0.000; Or = 0,280), and support the husband (p = 0.000; Or = 0,334) are relevance with exclusive breastfeeding. Knowledge, attitude, support the husband and place of birth are able to explain exclusive breastfeeding of 42.6% simultaneously. It is suggested to Public health Centre to do outreach the husband to improve knowledge of exclusive breastfeeding and its benefits. It is suggested to health service facilities to support program exclusive breastfeeding.